PENGARUH KEPEMIMPINAN DAN DISIPLIN TERHADAP KINERJA DOSEN STMIK DUMAI - Mardayulis Mardayulis; Mufti Hasan Alfani (JURNAL CAFETARIA, 2023)
The purpose of this study was to determine and analyze the influence of leadership and work discipline partially and simultaneously on the performance of lecturers at STMIK Dumai. This type of research uses associative research. The population of this study were 30 permanent and non-permanent lecturers at STMIK Dumai, while the sample in this study was 30 respondents. The type of research data used is primary data, data collection techniques using questionnaires, literature study, observation. Data analysis techniques used data quality tests, multiple linear regression, classical assumptions and hypothesis testing. Based on the results of the study, it was shown that partially leadership and work discipline had a positive and significant effect on lecturer performance in carrying out their duties at STMIK Dumai. Simultaneously it shows that leadership and work discipline have a positive and significant effect on the performance of lecturers at STMIK Dumai. The coefficient of determination shows that leadership and work discipline have a very strong relationship to the performance of lecturers found at STMIK Dumai. Lecturer performance can be explained by leadership and work discipline found at STMIK Dumai by 92.6% and the remaining 7.40% can be explained by other variables outside the scope of research that were not carried out in this study.